If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 + -3(2k + -4) = 18 Reorder the terms: -6 + -3(-4 + 2k) = 18 -6 + (-4 * -3 + 2k * -3) = 18 -6 + (12 + -6k) = 18 Combine like terms: -6 + 12 = 6 6 + -6k = 18 Solving 6 + -6k = 18 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -6k = 18 + -6 Combine like terms: 6 + -6 = 0 0 + -6k = 18 + -6 -6k = 18 + -6 Combine like terms: 18 + -6 = 12 -6k = 12 Divide each side by '-6'. k = -2 Simplifying k = -2
| a/3=-0.2 | | (9x+5)-(12x+7)= | | 3.4(2x+5)=-.2(2x+5) | | 12.3x=27.06 | | .5x+5=.33333333333333333333333333333333x+7 | | 4x^2(x-1)=0 | | 418=22x | | 1/4÷2/7= | | 28-4x/3=x | | 6-x=d | | 2x-44=-3 | | 12=8-f | | 4x+5y-6x-y= | | .07x+x=5 | | X+2.6=58.4 | | 12.25xy= | | X+0.75=12.25 | | f(n)=5n+4n | | .2(b+10)-7=.3333333333333333333333333333333(b-9) | | 12.2=m+18.2 | | 10p^2-100p+20000=0 | | -6y-3=3y+15 | | .2(b+10)-7=.333333333333333333333(b-9) | | -7(f+1)=5(f-2) | | -6x-13=x-23 | | x-y=31 | | x^2-6x-4=8 | | (2x+9)+x=90 | | -27.4=p-8.8 | | x+(3*3*3)=3*X-(10*10) | | 0.5(8x-16)=0.666(6x+12) | | h=1+30t-5t^2 |